A Visigoth Chief Alaric and the Sack of Rome by the Visigoths in 410 AD as Viewed in the “Chronicle” of John of Nikiu: Narratives of a Catastrophe or Religion-Political Clashes? - Evgeniy Mekhamadiev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
A Coptic bishop of the city of Nikiu in the Nile Delta John of Nikiu (the second half of the 7th c. AD) is famous for his only text – “Chronicle”, which is narrating about events from the Creation to the 640s, but it’s hard to treat the genre peculiarities of this work. Anyway, John intensively used the works of Greek-speaking church historians of the first half of the 5th c., that of Socrates Scholasticus and Hermias Sozomenos, in this way, a comparison of their evidence will enable not only to scan genre features of John’s “Chronicle”, but also to represent special points of his world-view. To make this comparison, the author of present paper chose an event prominent for the Late Roman Empire – a sack and capture of Rome by Visigoth chief Alaric in 410 AD. Describing Alaric’s deeds, John paid main attention not to plunders and destructions made by Goths in Rome, but to plots of the Senators against West Roman Emperor Honorius (395–423), while Greek church historians (including even Arian Philostorgius) depicted in depth strictly a siege and plundering of Rome. In this way, the author of the paper attempts to clear, why John neglected a meaning of destructions made by Alaric in Rome. In contrast to Greek historians, John doesn’t label Alaric as barbarian, he even doesn’t think on capture of Rome as on turning-point and tragic event, to John’s view it’s a routing event happened in the frameworks of political clashes and strife within West Roman Empire. What is most essential is that John doesn’t see in Rome’s capture a sign of God’s Providence, Alaric for him is a tool only of political clash between the Senators and the Emperor. To sum up, John actively combined traditions of two genres – secular and church history-writing, his work may be assessed not as chronicle as such, but rather as a mixture of church and secular (pagan) histories.